ANALISIS MANAJEMEN PRODUKSI TEPUNG TAPIOKA DI PT GUNUNG SUGIH KABUPATEN LAMPUNG TENGAH - Rosi Jayanti; Dwi Haryono; Sumaryo Gitosaputro (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to study the flow of tapioca agro-industry raw material procurement and how to manage tapioca flour agro-industry raw material procurement. This study uses a case study method at PT Gunung Sugih. Research respondents are owners and agro-industry companies and suppliers of agro-industrial raw materials selected by the candidates. Data analysis methods used are descriptive qualitative (raw material procurement planning and management applications) and quantitative descriptive (income analysis). The results showed that the five of the six components of raw material procurement were correct, except the inventory component, PT Gunung Sugih had approved the management function in all agro-industry activities. The agroindustry could be considered profitable because the results of the analysis of the income statement of the agro-industry gained a net profit of IDR8,190,800,833. Key words: agro-industry, cassava, profit, raw material